Clinical Significance of Nadir Hemoglobin in Predicting Neurologic Outcome in Infants With Abused Head Trauma - Lee, En-Pei; Zhao, Lu-Lu; Hsia, Shao-Hsuan; Lee, Jung; Chan, Oi-Wa; Lin, Chia-Ying; Su, Ya-Ting; Lin, Jainn-Jim; Wu, Han-Ping (Frontiers in Pediatrics, 2020)
Backgrounds: Traumatic brain injury (TBI) is a leading cause of pediatric morbidity and mortality. This study aimed to determine the role of anemia in predicting the neurologic outcome and mortality in infants with traumatic intracranial hemorrhage (ICH). Methods: Children aged less than 1 year diagnosed with traumatic brain injury complicated with ICH were selected and analyzed. Initial presentations, results of brain computed tomography scans, and hemoglobin (HB) levels were recorded. Outcomes were evaluated at discharge and six months later by using the Pediatric Cerebral Performance Category (PCPC) Scale. The receiver operating characteristic (ROC) curve was applied to determine the ideal cutoff values for HB levels for predicting poor neurologic outcomes. Results: In the study, of the 124 infants; fifty (40.3%) infants achieved a favorable neurologic outcome (PCPC ≦ 2) and 74 (59.7%) had poor neurologic outcomes (PCPC ≧ 3). Infants with poor neurologic outcomes had lower HB on admission, nadir HB (p<0.01). Based on the results of multivariate logistic regression analysis, the nadir HB was a predictor of poor neurologic outcomes at discharge and six months later in both abused and neglected groups, but only the initial Glasgow Coma Scale remained a predictor for mortality. Nadir HB had the largest area under the ROC curve for predicting poor neurologic outcomes in both groups of infants. The cutoff values of nadir HB for poor neurologic outcomes were 9.36 and 8.75 g/dl in the abused and neglected group, respectively. Conclusions: We determined the best cutoff value of nadir HB as 9.35 g/dl for predicting poor neurologic outcomes in infants with traumatic ICH. Furthermore, the cutoff value of nadir HB in predicting poor neurologic outcomes in infants caused by abuse and neglect were taken as 9.36 and 8.75 g/dl respectively.